2019
DOI: 10.2340/00015555-3286
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Study of Rosacea and Risk Factors in Women with Frontal Fibrosing Alopecia

Abstract: SIGNIFICANCEThe association between frontal fibrosing alopecia and rosacea is not clear. In this cross-sectional study, including 99 women with frontal fibrosing alopecia and 40 controls, women with frontal fibrosing alopecia presented a higher prevalence of rosacea than the controls did (61.6% vs. 30%), especially those with severe grades of alopecia (77.8% in grade V vs. 33.3% in grade I). Moreover, perifollicular erythema, higher body mass index and lower progesterone levels were associated with a higher ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…In a 355 patient cohort, the rate of early menopause (14%) was higher than in the general population (6%); moreover, 13% of patients had undergone a hysterectomy [ 3 ]. The mean time to the diagnosis reported in different studies is about 3.4 to 5.3 years [ 3 , 13 , 19 ]. Assessing the exact duration of the disease can be difficult sometimes, because its slow progression makes it complicated for the patient to detect the real time of onset.…”
Section: Epidemiology and Demographic Datamentioning
confidence: 99%
See 3 more Smart Citations
“…In a 355 patient cohort, the rate of early menopause (14%) was higher than in the general population (6%); moreover, 13% of patients had undergone a hysterectomy [ 3 ]. The mean time to the diagnosis reported in different studies is about 3.4 to 5.3 years [ 3 , 13 , 19 ]. Assessing the exact duration of the disease can be difficult sometimes, because its slow progression makes it complicated for the patient to detect the real time of onset.…”
Section: Epidemiology and Demographic Datamentioning
confidence: 99%
“…In fact, a recent study about hormonal dysfunction found that LPP is associated with androgen excess (testosterone or DHEAS), whereas FFA is related to androgen deficiency (32.1% of patients) [ 52 ]. According to these findings, DHEAS and androstendione have been found to be lower in women with FFA compared to a control group [ 19 , 53 ]. Moreover, abnormal estrogen and testosterone values have been associated with lesser disease activity [ 18 ].…”
Section: Aetiopathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…It is a lymphocytic scarring alopecia characterized by progressive recession of the frontal and temporoparietal hairline. The eyebrows, eyelashes, and body hair can be affected [51,52].…”
Section: Cicatricial Alopeciamentioning
confidence: 99%